2013
DOI: 10.4028/www.scientific.net/amr.683.385
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Wear on PEEK-PTFE Hybrid Radial Bearings

Abstract: In this paper, the wear performance of hybrid radial bearing (PEEK-PTFE and alumina ball) was investigated. For effective operation of equipment in clean energy facilities environment, the PEEK-PTFE hybrid bearings was developed. Radial PEEK-PTFE hybrid bearings were produced by machining and their rolling contact fatigue (RCF) behavior under non-lubricated condition was carried out. PEEK accumulation layer with PTFE and graphite appeared on the bearing's inner ring under 600-3000 rpm rotation speed. Due to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…PEEK and PI [1][2][3][4][5] are two kinds of widely used engineering polymer materials as roller bearing cages and rings in ceramic bearings [6][7][8]. Ceramic bearings are developed for industrial applications under extreme and special operating conditions in water.…”
Section: Introductionmentioning
confidence: 99%
“…PEEK and PI [1][2][3][4][5] are two kinds of widely used engineering polymer materials as roller bearing cages and rings in ceramic bearings [6][7][8]. Ceramic bearings are developed for industrial applications under extreme and special operating conditions in water.…”
Section: Introductionmentioning
confidence: 99%
“…The RCF tests of PEEK-PTFE radial bearings were done using the RCF test machine which was developed by Kida's group [1][2][3][4]6]. Figure 3 shows a schematic illustration of the RCF testing machine.…”
Section: Rolling Contact Fatigue (Rcf) Testmentioning
confidence: 99%
“…PEEK (Poly-Ether-Ether-Ketone) and PTFE (Poly-Tetra-Fluoro-Ethylene) have good mechanical features such as heat and corrosion resistance. In our previous studies on PEEK radial bearings [1][2][3][4], the effect of radial load on bearing life in dry conditions was investigated. Mizobe et al found that the wear resistance of the PEEK hybrid thrust bearing with a PTFE retainer was superior to that without the PTFE retainer [5].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has a long operation life of more than 1.0 × 10 7 revolutions and the tendency towards a lower load yields a longer life. 8) (b) Good Availability These oil-free plastic bearings are widely utilized currently in the food and medical industries that require cleanliness. Owing to this industrial application, PEEK-PTFE ball bearings are easy to acquire.…”
Section: Ball Bearingmentioning
confidence: 99%